(untitled) (Nativa, 2024)
ABSTRACT: Wood densification is a process combining heat, moisture, and mechanical action to improve the density of wood without changing the characteristics of wood, including density, water repellency effectiveness (WRE), modulus of rupture (MOR) and compressive strength (CS). This study aims to identify and evaluate the effect of the compression parameter on some physical and mechanical properties of Acacia hybrid wood. Design Expert 11.0.8 software was used to design experiments, and the experimental data was processed using SPSS Statistics 22.0. The obtained results indicate that the higher the compression ratio is, the higher the increased density of the compressed wood will be achieved. As the temperature and compression time increase, the density increases. However, the density of compressed wood will decrease slightly when the temperature and the time exceed 180°C and 180 minutes, respectively. After treatment, Acacia hybrid wood has good WRE values of 15.12 % to 31.21%. MOR and CS increased with the growing ratio, temperature and time of compression but tended to fall when the temperature and time surpassed 160°C and 120 minutes. Keywords: thermomechanical compressed wood; Acacia hybrid wood; compression ratio; density; water repellency effectiveness. Efeitos do tratamento termomecânico em propriedades da madeira de um híbrido de Acacia RESUMO: A densificação da madeira é um processo que combina calor, umidade e ação mecânica para melhorar a densidade da madeira sem alterar suas características, incluindo densidade, eficácia de repelência à água (WRE), módulo de ruptura (MOR) e resistência à compressão (CS). Este estudo tem como objetivo identificar e avaliar o efeito do parâmetro de compressão em algumas propriedades físicas e mecânicas da madeira híbrida de acácia. O software Design Expert 11.0.8 foi usado para projetar experimentos, e os dados experimentais foram processados usando o SPSS Statistics 22.0. Os resultados obtidos indicam que quanto maior a taxa de compressão, maior será o aumento da densidade da madeira comprimida. À medida que a temperatura e o tempo de compressão aumentam, a densidade aumenta. No entanto, a densidade da madeira comprimida diminuirá ligeiramente quando a temperatura e o tempo excederem 180 °C e 180 minutos, respectivamente. A madeira híbrida de acácia, após o tratamento, apresenta boa WRE com valores de 15,12% a 31,21%. MOR e CS aumentaram com a taxa de crescimento, temperatura e tempo de compressão, mas tenderam a cair quando a temperatura e o tempo ultrapassaram 160°C e 120 minutos. Palavras-chave: madeira comprimida termomecânica; madeira híbrida de acácia; taxa de compressão; densidade; eficácia de repelência à água.